Changes In The Activities Of The Archives Of The Uzbek SSR (As An Example Of The Ferghana Valley) (Texas Journal of Multidisciplinary Studies, 2025)
This article provides information about the establishment of archives in the Uzbek SSR, changes in the activities of the Ferghana Valley archives, attention paid to archives, and work carried out to preserve documents.